Temperature tolerance of European fish species based on thermal maxima in southern Baltic Sea-basin streams - Grzegorz Radtke; Rafał Bernaś (Ecological Indicators)
Evaluation of the thermal requirements of fish species is particularly important given ongoing climate change and warming trends. Assessing thermal tolerance reveals the potential a species has to persist, spread, or disappear. For this purpose, we determined an upper limit of thermal tolerance for 22 European fish and lamprey species based on temperature maxima in streams in northern Poland (southern Baltic Sea catchment) and sampling of fish species. We related the observed thresholds of the realized thermal niches to data from the literature on tolerance and lethal temperatures as boundaries of the fundamental niches of species. Additionally, upper tolerance boundaries are reported here for the first time for some species. For all species, the upper limit of physiological endurance (lethal temperature) was clearly higher than the tolerance threshold. For most cold-water and cool-water species, the upper limits of thermal tolerance matched or were similar to the field data. For the remaining species, mainly Cypryniformes, the tolerance thresholds (obtained from laboratory experiments) were distinctly higher than the temperatures reached in the stream environments. Alpine bullhead (Cottus poecilopus) was found to be an extreme representative of cold water stenotherms. It can be concluded that species for which the upper tolerance limit is < 28 °C live at the “warm edge” of their distribution in the studied region, and, therefore, ongoing warming will decrease their range. However, species whose tolerance thresholds are > 30 °C have a “thermal reserve” and are not immediately threatened by warming trends.